2015
DOI: 10.4252/wjsc.v7.i2.470
|View full text |Cite
|
Sign up to set email alerts
|

CD271 as a marker to identify mesenchymal stem cells from diverse sources before culture

Abstract: Mesenchymal stem cells, due to their characteristics are ideal candidates for cellular therapy. Currently, in culture these cells are defined by their adherence to plastic, specific surface antigen expression and multipotent differentiation potential. However, the in vivo identification of mesenchymal stem cells, before culture, is not so well established. Pre-culture identification markers would ensure higher purity than that obtained with selection based on adherence to plastic. Up until now, CD271 has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 60 publications
7
106
0
Order By: Relevance
“…Literature has indicated that CD271 can be found in neural crest stem cells and is considered as one of neural crest cell markers [47]. Besides, CD271 has been proposed as a marker to identify the isolated mesenchymal stem cells [48]. On the other hand, SOX10 maintained multipotency and inhibited neuronal differentiation, but was permissive for glial differentiation of neural crest stem cells [49].…”
Section: Discussionmentioning
confidence: 98%
“…Literature has indicated that CD271 can be found in neural crest stem cells and is considered as one of neural crest cell markers [47]. Besides, CD271 has been proposed as a marker to identify the isolated mesenchymal stem cells [48]. On the other hand, SOX10 maintained multipotency and inhibited neuronal differentiation, but was permissive for glial differentiation of neural crest stem cells [49].…”
Section: Discussionmentioning
confidence: 98%
“…3 CD271 + has also been described as the most specific marker for bone marrow-derived mesenchymal stem cells (BM-MSCs) and adipose-derived stem cells (ASCs). 4 However, consensus has yet to be reached with regard to their antigen expression profile. 5 The inconstant nature of surface marker expression as these cells are removed from their native environment and expanded ex vivo merely worsens the surrounding controversy.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Furthermore, HMSC with special cluster of differentiation, such as CD 37 , CD 90 , and CD 40 with little increased expression of CD 14 , CD 34 , CD 45 , and human leucocyte-DR (HLA-DR) can differentiate to osteoblast cells (4). Researchers exploit HMSC from different sources, such as dental tissue, endometria menstrual, blood, peripheral blood, placenta and fetal membrane salivary gland, skin, synovial fluid, foreskin, endometrium amniotic fluid, subamniotic umbilical cord lining membrane, and Wharton jelly (5).…”
Section: Contextmentioning
confidence: 99%